'More Power to the Women': Gender and Australia's Animal Justice Party. Issue 106 (1st October 2020) - Abbey, Ruth
ABSTRACT: Scholars have long noted the strong presence of women in animal advocacy movements. The twenty-first century has seen the rise of political parties devoted to animal issues across the western world. We do not yet know to what extent the gender dynamics of animal advocacy movements will carry over to these political parties, and the few scholars who have studied animal parties have not yet paid attention to the issue of gender. As a way of identifying and exploring the question of gender, this article reports the findings of an interview-based study of members of Australia's Animal Justice Party (AJP), exploring their views on gender in the context of animal advocacy. In addition to being the first study of the role of gender in animal parties, this is the first to use interviews as a way of probing the motivations of those who support such parties. It shows the feminist ethics of care to be a central part of these motivations. The article engages with the issue of women's presence in animal advocacy as well as men's absence. It also considers animal parties as a potential avenue for women to exercise political leadership.